Beyond Java: dr. Rubini, Political Exile, and the Dynamics of Peripheral Nationalism in Colonial Indonesia (1920–1944) - Prabowo, Mohammad Rikaz (Diakronika, 2025)
Rubini was a national movement activist in West Kalimantan who, in 1939, became the chairman of Parindra and then led the resistance against Japan from 1942 to 1944. This study aims to explain his background and role in the struggle against colonialism during the Dutch and Japanese eras. The study uses historical methods, including heuristics, verification, interpretation, and historiography. Based on the analysis, the following conclusions are drawn: First, Rubini was born into an educated and respected aristocratic family in Sundanese society. During his time as a STOVIA student, he interacted with national political movements such as the Paguyuban Pasundan, which developed a nationalist attitude. Second, in 1939, he became one of the heads of the West Kalimantan commissariat; through exemplary cooperation and efforts, this party became a major political force there at that time. Third, Dr. Rubini, along with other activists, founded Nissinkwai (1942), which pretended to collaborate with the Japanese. In 1943, Rubini led an underground resistance movement. Unfortunately, this action was discovered by the Japanese; he and other activists were arrested and executed on June 28, 1944. The struggle he led was one of the factors that triggered the Dayak resistance in 1945 and influenced his colleagues' efforts to maintain independence. This research contributes to the historiography of the national movement and the Japanese occupation, particularly in the context of local history in West Kalimantan. This research adds to the list of doctors who participated in the struggle for independence in the nation's history.